Kajian Literatur Strategi Pembelajaran IPAS Berbasis Deep Learning - Okyranida, Indica Yona; Bhakti, Yoga Budi (UNIVERSITAS INDRAPRASTA PGRI, 2023)
Deep learning-based instructional strategies have been increasingly applied in Science and Social Studies (IPAS) education to enhance students' conceptual understanding and critical thinking skills. This study aims to review various IPAS teaching strategies that adopt deep learning principles through a systematic analysis of literature from the past five years. The research method employed is a systematic review of academic sources discussing the implementation of deep learning strategies in IPAS education. The synthesis results indicate that strategies such as Project-Based Learning, Problem-Based Learning, and collaborative learning are highly effective in improving student learning outcomes. Additionally, the integration of digital technology plays a crucial role in supporting the implementation of deep learning-based education. However, several challenges in its application were identified, including limited resources and teacher readiness in designing lessons that facilitate in-depth exploration. Therefore, further development of adaptable implementation models and enhanced teacher competencies are necessary to optimize deep learning-based instructional strategies in IPAS education.